Governmentality and gendered realities: experiences from the Philippines' cash transfer programme. Issue 3 (3rd April 2021) - Alinsunurin, Maria Kristina G.
ABSTRACT: Social policies such as conditional cash transfer programmes (CCTs) have technical and measurable outcomes which are favourable for countries in the Global South, where development impact on health and education matters. This paper presents grounded narratives of women beneficiaries of the Philippines' Pantawid Pamilyang Pilipino Program (4Ps), and outlines how conditionalities have reconfigured beliefs and conduct among these women. Using the concept of governmentality, the process of meeting programme conditions presents itself as a form of exercising power to configure the habits and beliefs of the population. The paper contributes to the critical discourses, challenges and normative views on the impact of CCTs.